Adipose Genes Down-Regulated During Experimental Endotoxemia Are Also Suppressed in Obesity - Shah, Rachana (Endocrine Society, 2012)
CONTEXT: Adipose inflammation is a crucial link between obesity and its metabolic complications. Human experimental endotoxemia is a controlled model for the study of inflammatory cardiometabolic responses in vivo. OBJECTIVE: We hypothesized that adipose genes down-regulated during endotoxemia would approximate changes observed with obesity-related inflammation and reveal novel candidates in cardiometabolic disease. DESIGN, SUBJECTS, AND INTERVENTION: Healthy volunteers (n = 14) underwent a 3 ng/kg endotoxin challenge; adipose biopsies were taken at 0, 4, 12, and 24 h for mRNA microarray. A priority list of highly down-regulated and biologically relevant genes was validated by RT-PCR in an independent sample of adipose from healthy subjects (n = 7) undergoing a subclinical 0.6 ng/kg endotoxemia protocol. Expression of validated genes was screened in adipose of lean and severely obese individuals (n = 11 per group), and cellular source was probed in cultured adipocytes and macrophages. RESULTS: Endotoxemia (3 ng/kg) suppressed expression of 353 genes (to <67% of baseline; P < 1 × 10(−5)) of which 68 candidates were prioritized for validation. In low-dose (0.6 ng/kg) endotoxin validation, 22 (32%) of these 68 genes were confirmed. Functional classification revealed that many of these genes are involved in cell development and differentiation. Of validated genes, 59% (13 of 22) were down-regulated more than 1.5-fold in primary human adipocytes after treatment with endotoxin. In human macrophages, 59% (13 of 22) were up-regulated during differentiation to inflammatory M1 macrophages whereas 64% (14 of 22) were down-regulated during transition to homeostatic M2 macrophages. Finally, in obese vs. lean adipose, 91% (20 of 22) tended to have reduced expression (χ(2) = 10.72, P < 0.01) with 50% (11 of 22) reaching P < 0.05 (χ(2) = 9.28, P < 0.01). CONCLUSIONS: Exploration of down-regulated mRNA in adipose during human endotoxemia revealed suppression of genes involved in cell development and differentiation. A majority of candidates were also suppressed in endogenous human obesity, suggesting a potential pathophysiological role in human obesity-related adipose inflammation.